SYSTEMATICS OF VAGRANTINI BUTTERFLIES (LEPIDOPTERA: NYMPHALlDAE). PART 2. DISCUSSION ON CLADES AND CHARACTER DISTRIBUTIONS - Djunijanti Peggie (BRIN Publishing (Penerbit BRIN), 2004)
Cladistic IIl1alysis oj the t n do-Austrutian heliconiine butterflies showed that they belong to the Heliconiinae. Tile name Yagrantini was suggested by Pcnz and Peggie (2003) to include Vindula, Smerina, Vagrans, Phalanta, Cupha, Terinos. Lachnoptera, Algia, Algiachroa, and Cirrochroa. Vindula is ShOWlllISsister grollp to the rest oj the gellem, and Terinos [orins a sister-group relationship with Lachnoptera and the Cirrochroa group-oj-genera. The /Ilollophyly oj the Cupha group-oj-genera and the Cirrochroa group-oj-genera lire supported.